Physiotherapy Management of Torticollis Sinistra at Ulin Banjarmasin Hospital: Case Study - Nafiah Nafiah Nafiah (Politeknik Unggulan Kalimantan, 2024)
Torticollis is a condition the head in a tilted position, with the chin pointing to one shoulder. This type of research is a case study conducted at the Physiotherapy Clinic of ULIN Banjarmasin Hospital. The research time was July 2023. The subject of this study was a child aged 1 year and 3 months with Torticolis sinistra. After a physiotherapy examination, the results there was a contracture of m.sternoleidomatoideus on the sinistra side, moderate head and neck deviation < 45 °, weakness of the lateral flexor and rotator muscle groups sinistra head and neck, limited scope of motion of flexion, extension, lateral flexion and rotation sinistra head and neck, the patient is less free when looking towards the left, limitations when feeding by turning his head to the left. Furthermore, patient given the intervention of massage, stretching, active and active assisted exercise. Obtained evaluation results that there is an improvement in spasm and contracture. While in other problems such as muscle strength, joint range of motion, posture, and functional activities there has been no improvement due to intrinsic factors such as the difficulty of accustoming children to opposite positions during their daily activities and so on. Further research needs to be carried out that is more detailed.